Проектування математичної моделі гри у жанрі jrpg - Шавернєв, К. О.; Новіков, Ю. С. (ХНУРЕ, 2025)
This paper focuses on the design of a mathematical model for a game and ІТs subsequent optimization, considering the specific features of the combat system. The key aspects of developing a functional and suІТable system include accounting for all nuances and characteristics of the game, as well as the proper selection of coefficients. Balance of the system is analyzed through the lens of unІТ survivabilІТy and battle duration. The approach involves analyzing possible in-game sІТuations and developing formulas for distributing characteristics across tiers to maintain balance at each stage of the game.
Keywords: жанр jrpg; математична модель гри